Delivery Health Service Utilization and Barriers to Access in Lao People’s Democratic Republic (PDR): An Analysis of MICS Data 2023 - Amaliah, Lili; Supriatin, Supriatin; Sadli, Mohamad; Maretalinia, Maretalinia (Journal of Health and Nutrition Research, 2025)
Technological advances and accessibility influence the utilization of health services in today's world, but barriers still exist. This study aims to comprehensively analyze the utilization of maternal health services and the barriers that hinder access in the Lao People's Democratic Republic (PDR). This study analyzed 2023 MICS data from 3,754 women in the Lao People's Democratic Republic, examining maternal health service utilization. The dependent variable was categorized as utilization or non-utilization, while the independent variables included demographics, geography, decision-making power, and health system factors. Descriptive statistics, chi-square tests, and binary logistic regression were used for data analysis. This study found that of the 3,754 respondents, 2,930 people used health services to give birth. The chi-square test showed that age, education, residence, region, decision making, insurance ownership, and wealth index were significantly associated with using maternal health services. Multivariate analysis showed that higher education was the strongest predictor of health service use (OR = 20.90), with geographic factors, wealth inequality, and shared decision-making. Areas without road access and the poorest wealth groups were less likely to use services, while shared decision-making increased the likelihood by 45%. It is recommended that higher education be promoted, road access improved, and shared decision-making be encouraged to increase the utilization of maternal health services, especially among the poorest communities and those living in rural areas.